Role of breast crawl in maternal health and wellbeing - Tiwari, Varsha; Singh, Neelam; Purohit, Ashish; Shyam, Saroj (International Journal of Medical Research and Review, 2015)
Background : Initiation of breast-feeding within hour of birth is very crucial. Except human other mammalian species start immediate breast feeding of their newborn. Human delays the breast feeding from hours to days. it is also known that even human babies can start breast feeding on their own like the young ones of the animals .Every newborn, when placed on her mother’s abdomen, soon after birth, it havethe capability to find her mother’s breast all on her own & to decide when to take the first breast feed this is known as breast crawl. These advantages not only protect mothers health in several ways, also benefits whole family, emotionally and economically. Methods: A prospective cohort observation study done on 200 research cases & similarly control cases were selected from full term newborn babies delivered vaginally, in Dr. B. R. Ambedkar Memorial. Hospital. andpt JNM medical college Raipur (C.G.). Results: Out of 200 full term babies, 166 babies able to successfully crawl within in 50 min. Out of 166 breast crawl mothers–(1) 95.% mothers had early expulsion of placenta. (2) 96% mothers had decrease in uterine size. (3) 100% breast crawl mothers were satisfied. (4) 93% mother had no anemia in post partum period of same pregnancy. Conclusions: This is new research study in India so far. Breast crawl has very beneficial effect on health of mother by preventing postpartum hemorrhages, anemia, breast feeding failure & sense of wellbeing.